Walden : life in the woods - Thoreau, Henry David, 1817-1862 (Gibbs Smith, 2017)
"Experience a year in the life of Thoreau at Walden Pond in this classic work. Visit the bean-field, the village, and the ponds; learn about our brute neighbors, the higher laws of nature and humankind, and the benefits of reading and solitude. Henry David Thoreau was an American author, poet, abolitionist, naturalist, tax resister, development critic, surveyor, historian, philosopher and leading transcendentalist. His writings on natural history and philosophy have become two sources of modern-day environmentalism."